Propriedades mecânicas e retração do concreto com adição de cinza de casca de arroz natural, sem beneficiamento de moagem - Meinerz, Leticia Ribeiro Meira (2009)
To present research has for objective investigate the technical feasibility of the job of rice husk ask ungrounded, in concretes for structural ends. This study tries the mechanical properties of axial compression strength, tensile strength by diametrical compression, elasticity modulus and total shrinkage of concretes molded with addition of RHA natural, with contents of 15% and 25% in substitution in mass of cement CP II-F, in the forms ground in mill of balls and natural (without grinding), and compared with the concrete of reference, with 0.45, 0.55, and 0.65 water/cementations materials relationships. Were tested for resistance to axial compression on the ages of 7, 28 and 91 days, resistance to diametric compression by 28 and 91 days, modulus of elasticity at 28 and 91 days and total shrinkage at 28, 91 and 300 daysThe results indicated that technical feasibility exists for the use of rice husk ash ungrounded, for the content of 15% of substitution, in structural concrete. The values from tests of concrete with 15% of RHA without grinding developed axial compression strength over the reference, lower shrinkages, tensile strength by diametrical compression and elasticity modulus lower however with not significant falls.